Aspirin Allergy Desensitization in Cerebrovascular Disease: A Report of Two Cases, Literature Review and Management Guide for the Neurointerventionalist. Issue 1 (January 2014) - Zuckerman, Scott L; Seder, David B; Tsujiura, Crystiana; Cushing, Deborah; Gallup, Holly; Mocco, J; Hanel, Richard A; Ecker, Robert D
Aspirin (ASA) is the mainstay of treatment in cerebrovascular and systemic vascular disease. ASA hypersensitivity can pose a challenge to achieving optimum medical management prior to and after neurointerventional treatment. Desensitization to ASA is well described in the allergy and cardiovascular literature, but there are no similar discussions specific to neurointervention. The purpose of our study was to describe our experience with ASA hypersensitivity management and review the relevant literature. Two cases of patients with symptomatic cerebrovascular disease requiring neurointervention who were successfully desensitized to their ASA hypersensitivity prior to treatment are described. The subsequent literature is reviewed. Several ASA desensitization protocols exist and have been proven to successfully treat ASA hypersensitivity and allow for ASA therapy to be safely initiated. We describe several previously published protocols. ASA desensitization is a safe and simple way to manage ASA hypersensitivity. We provide comprehensive management guidelines for the neurointerventionalist engaging in ASA desensitization.